DIMENSI SUFISTIK DALAM PUISI “TAPI” KARYA SUTARDJI CALZOUM BACHRI - Fajar Setio Utomo; Rosida Erowati (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Literary work which inflames a feeling of divine love and the prophetic spirit that led to the transcendental intensity enliven the Indonesian literary treasures. In this regard, it is worth to note the exiistence of  Sutardji as a sufi poet. Many critics and observers who see Sutardji as Indonesian poet who has an intensity appreciation of divinity (monotheism) and high religiosity.  It  is proven  by  the  presence of  poetry O, AMUK, and  AX that sensationaized Indonesia poetry.The research method that is used in this research is descriptive qualitative method.The data collection was done by using library technique and record, while data analysis was performed by using the method of semiotic reading model which consists of three stages of analysis, namely; syntax, semantic, and pragmatic.Poetry But, in this case, is loaded with ideas of Sufism Wahdatul Wujud, which shows the proverbial human  existence with the  existence of God, the proverbial human dimension and the divine dimension, merging creature with the Creator, with the result that there  are  two dimensions  of Sufism,  the transcendent  dimension and immanent dimension.